Managerial Insights into the Effects of Interactions on Replacing Members of a Team - Solow, Daniel; Vairaktarakis, George; Piderit, Sandy Kristin; Tsai, Ming-chi (Management Science, 2002)
A mathematical model is presented for studying the effects of interactions among team members on the process of replacing members of a team in an organization. The model provides the ability to control the number of members that interact with each individual on the team. Through the use of analysis and computer simulations, it is shown how the amount of interaction affects the tradeoff between the expected performance and the number of replacements and interviews needed to find a good team using various replacement policies. New managerial insights into this process—such as the fact that it is not necessarily optimal to replace the worst-performing team member—are provided.